Experience and Legal Ethics Teaching - James E Moliterno (Legal Education Review)
I have been teaching law on a full-time basis for almost forty years, including courses in legal ethics for thirty of those forty years. As any ageing teacher does, I suppose, I like to think of my teaching as effective. With a few exceptions, the teaching techniques I have appropriated or invented for classes in legal ethics have worked reasonably well. Within that, there are two techniques that have worked well enough to justify suggesting them to other teachers. One of these is the use of daily (or at least weekly) writing by students. The other is teaching in and from the clinic, with stories told and “dilemmas” described by students about their real clients.